2019
DOI: 10.1108/ijsms-01-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

The negative spillover effect in sports sponsorship

Abstract: Purpose The purpose of this paper is to examine a possible negative spillover effect in sports sponsorship to answer whether the sponsored team’s poor performance will have a negative effect on audiences’ trust in its sponsor’s brand. The authors further analysed whether the audience’s attitude towards the team plays a mediating role and whether the audience’s personality type (active vs passive) plays a moderating role in this negative spillover effect. Design/methodology/approach Three experimental studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…Trust has been found to play a significant role in shaping attitudes towards sport team sponsors (Alonso Dos Santos et al, 2016), but sponsors may prefer partnerships with sport events due to the potential negative impact of poor team performance on consumer trust in the sponsor's brand (Yuan et al, 2019). Studies by Zhang et al (2019) and Lee et al (2014) have shown how trust can be transferred from the event to the host destination, and that stronger identification with the event or organiser positively influences the perception of fit (Deitz et al, 2012; Koo & Lee, 2019; Sirgy et al, 2008), potentially presenting challenges for sport events with negative public images (Kulczycki & Koenigstorfer, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Trust has been found to play a significant role in shaping attitudes towards sport team sponsors (Alonso Dos Santos et al, 2016), but sponsors may prefer partnerships with sport events due to the potential negative impact of poor team performance on consumer trust in the sponsor's brand (Yuan et al, 2019). Studies by Zhang et al (2019) and Lee et al (2014) have shown how trust can be transferred from the event to the host destination, and that stronger identification with the event or organiser positively influences the perception of fit (Deitz et al, 2012; Koo & Lee, 2019; Sirgy et al, 2008), potentially presenting challenges for sport events with negative public images (Kulczycki & Koenigstorfer, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to (Jensen, 2012), the better sports results and the higher athlete's ranking result in the more exposure an athlete should expect to earn for the sponsors. Previous studies also conveyed that the poor performance of a sports team negatively affects the audiences' brand trust towards the sponsor (Yuan et al, 2019). On top of that, the perceived losing team will lower customers' purchase intention of a sponsor's product (Ngan et al, 2011).…”
Section: A Introductionmentioning
confidence: 98%
“…Tal fato pode ser comprovado pela pesquisa realizada porSmith (2004) na qual o autor apresenta que existe uma relação direta entre performance desportiva e sucesso no patrocínio.Segundo o autor, quando uma equipe tem uma baixa performance, os torcedores tendem a associar essa performance ao patrocinador. No contexto chinês,Yuan et al, (2019) apresentam um estudo no qual uma empresa chinesa patrocina uma equipe de futebol local, porém, essa equipe tem uma baixa performance, o que resulta em associações negativas perante esse patrocinador, como "perdedor" e "fraqueza", atributos que nenhuma empresa gostaria de possuir (YUAN ET AL., 2019). Na mesma linha,Pope et al, (2009) demonstraram em seu estudo um efeito negativo do desempenho esportivo nas avaliações das marcas patrocinadoras.SegundoYuan et al, (2019), essa baixa performance pode afetar a confiança que o consumidor tem na marca patrocinadora, e essa confiança resulta em uma mudança de comportamento desse consumidor perante essa marca.…”
unclassified
“…No contexto chinês,Yuan et al, (2019) apresentam um estudo no qual uma empresa chinesa patrocina uma equipe de futebol local, porém, essa equipe tem uma baixa performance, o que resulta em associações negativas perante esse patrocinador, como "perdedor" e "fraqueza", atributos que nenhuma empresa gostaria de possuir (YUAN ET AL., 2019). Na mesma linha,Pope et al, (2009) demonstraram em seu estudo um efeito negativo do desempenho esportivo nas avaliações das marcas patrocinadoras.SegundoYuan et al, (2019), essa baixa performance pode afetar a confiança que o consumidor tem na marca patrocinadora, e essa confiança resulta em uma mudança de comportamento desse consumidor perante essa marca. Fazendo um paralelo ao modelo apresentado por no capítulo 4.6, quando a equipe tem uma baixa performance desportiva, os resultados básicos e de engajamentos podem ser afetados negativamente.…”
unclassified